Glossators and Commentators at the Strahov Library - Novák, Marek (Karolinum, 2025)
Private law in the Czech Republic, as in many countries, has its roots in Roman law, which reached its peak through codification by Emperor Justinian. However, modern civil codes are not directly based on Roman law source texts but on their later reception by medieval and modern jurists. This study aims to identify writings by authors belonging to the earliest stages of Roman law reception in the as-of-yet unsorted collection of the library of the Royal Canonry of Premonstratensians at Strahov. It discovers the works of glossators and commentators, analyses manuscripts, incunabula, and old prints and supplements the related data with examples of the used working methods. In addition, one of the results of the research was a set of proposals for correcting the library catalogue, which has already been implemented. The study therefore offers current shelf marks in alignment with the actual state of the collection and aims to serve as a practical guide for researchers interested in studying this segment of legal history.
Keywords: Právo